The Free Choice Principle as a Default Rule - Glavaničová, Daniela (Organon F, 2018)
It is quite plausible to say that you may read or write implies that you may read and you may write (though possibly not both at once). This so-called free choice principle is well-known in deontic logic. Sadly, despite being so intuitive and seemingly innocent, this principle causes a lot of worries. The paper briefly but critically examines leading accounts of free choice permission present in the literature. Subsequently, the paper suggests to accept the free choice principle, but only as a default (or defeasible) rule, issuing to it a ticket-of-leave, granting it some freedom, until it commits an undesired inference.
Keywords: default rule; Defeasibility; free choice permission; non-monotonic logic; paradox